Strategi Menghadapi Peserta Didik Remaja Melalui Pendekatan Empatik Dalam Bimbingan dan Konseling - Prabowo, Sugeng; Nisaa’k, Zulma Khoirotun; Khoiruddin, Raf’ul; Fathoni, Tamrin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Adolescence is a period marked by significant emotional, social, and physical transformations that affect a teenager’s identity, social interactions, and understanding of the world. During this time, adolescents often face identity confusion, anxiety, depression, and challenges in establishing healthy relationships with peers and parents. Thus, a sensitive and comprehensive approach is necessary to help them navigate these challenges. One such approach is the empathetic approach, introduced by Carl Rogers (1951) within the framework of humanistic therapy. Empathy, according to Rogers, involves understanding another person's feelings without judgment, and in the context of adolescents, it entails listening attentively, respecting their experiences, and providing a non-judgmental space for identity exploration. Research has shown that this empathetic approach can significantly benefit adolescents by enhancing their psychological well-being, improving their ability to manage stress, and fostering healthy interpersonal relationships. This article discusses the importance of empathy in supporting adolescents through various psychological issues, such as identity confusion, emotional fluctuations, peer pressure, bullying, and academic stress. The article also explores relevant theories, including Carl Rogers' Client-Centered Theory, Daniel Goleman's Emotional Intelligence, Paul Ekman’s Emotion Expression Theory, and Urie Bronfenbrenner’s Ecological Systems Theory. Furthermore, strategies for implementing an empathetic approach, such as active listening, providing emotional expression space, and avoiding judgment, are discussed. Ultimately, this article aims to provide insights and recommendations for parents, educators, and professionals to effectively support the emotional well-being of adolescents by integrating empathy into their interactions.